Congress of Contradictions: The Tenth Party Congress, March 1921 - Black, Clayton,; Pogorelskin, Alexis, (Historical Materialism Book Series ;, 2026)
The volume is a long overdue re-evaluation of the Tenth Party Congress, the first congress to follow the Civil War where the NEP era was launched. It therefore bears the distinction as the first of the six congresses under NEP. Often overlooked, the Tenth was also the last to see Lenin's full participation. The congress thus provides a crucial vantage point from which to view Lenin's intentions for the party and vision for the country as the new Soviet state began recovery following years of conflict. Ten contributors offer new perspectives on this crucial event of the early Soviet period. Several ask, was the congress a real turning point? Some insist that for most of the main figures in the regime, it was just that. While most scholars agree that the congress laid the foundation for the party up to the end of the regime, the volume offers alternative interpretations of an event that helped establish the Soviet state and set the terms for control by the Communist party.